LINS Curve in Romanian Economy - Emilian Dobrescu (Amfiteatru Economic)
The paper presents theoretical considerations and empirical evidence to test the validity of the Laffer in Narrower Sense (LINS) curve as a parabola with a maximum. Attention is focused on the so-called legal-effective tax gap (letg). The econometric application is based on statistical data (1990-2013) for Romania as an emerging European economy. Three cointegrating regressions (fully modified least squares, canonical cointegrating regression and dynamic least squares) and three algorithms, which are based on instrumental variables (two-stage least squares, generalized method of moments, and limited information maximum likelihood), are involved.